The Synthesis of Picolinamide-Supported Tetracoordinated Organoboron Complexes with Aggregation-Induced Emission Property - You, Gaoqiang; Xu, Liang; Wei, Yu (Frontiers in Chemistry, 2022)
The picolinamide-supported tetracoordinated organoboron complexes containing diaryl boronyl segments have been synthesized for the first time. Aryl trifluoroborates were utilized as the BAr2 sources to introduce different aryl motifs with diverse functional groups. The optical experiments discovered these five-membered boron-containing complexes were aggregation-induced emission (AIE) active, thus affording a new class of AIE molecules.